The Politics of Punishment Prison Reform in Russia, 1863–1917 - Adams, Bruce Friend 1946-2008 (NIU Series in Slavic, East European, and Eurasian Studies, 2019)
Bruce F. Adams examines how Russia's Main Prison Administration was created, the number of prisoners it managed in what types of prisons, and what it accomplished. While providing a thorough account of prison management at a crucial time in Russia's history, Adams explores broader discussions of reform within Russia's government and society, especially after the Revolution of 1905, when arguments on such topics as parole and probation boiled in the arena of raucous public debate